Mathematical Problem Posing
XXXI, 569 p. 148 illus., 52 illus. in color.
Keywords: This international review offers current findings on the art and science of problem posing and its multiple contributions to mathematics teaching, learning, training, and curriculum design. Diverse perspectives on problem posing frame the concept as a springboard for scientific inquiry and the process as a means to promote mathematical understanding across the primary and secondary grades. Problem posing is demonstrated as enhancing students' problem-solving skills, bolstering knowledge retention, and improving attitudes toward mathematics, and the book provides evidence-based strategies for its integration into both classroom work and teacher education. This information is particularly critical as mathematics-based knowledge continues to dominate technology and the sciences. Among the topics covered: Using digital technology for mathematical problem posing. Problem posing as a tool for identifying and developing mathematical creativity. Problem posing as providing students with content-specific motives. What high school teachers mean when they say "I pose my own problems." Problem posing as a motivational tool in primary school teacher training. Problem posing as an integral component of the mathematics curriculum. For mathematics educators as well as mathematics education researchers, Mathematical Problem Posing brings clarity and innovative understanding to a central element in the continuing progress of the field.